Genome assembly and population analysis of tetraploid marama bean reveal two distinct genome types - Jin Li; Christopher Cullis (Scientific Reports)
Abstract Tylosema esculentum (marama bean), an underutilized orphan legume native to southern Africa, holds significant potential for domestication as a rescue crop to enhance local food security. Well-adapted to harsh desert environments, it offers valuable insights into plant resilience to extreme drought and high temperatures. In this study, k-mer analysis indicated marama as an ancient allotetraploid legume. Using 21.5 Gb of PacBio HiFi data, the genome was assembled with two assemblers, HiCanu and Hifiasm, followed by scaffolding with Omni-C data from Dovetail Genomics (Cantata Bio) using HiRise, resulting in a 558.78 Mb assembly with near chromosome-level continuity (N50 = 22.68 Mb, L50 = 8). Repeats accounted for 58.43% of the genome. Phylogenetic analysis indicated a close relationship with Bauhinia variegata and Cercis canadensis, diverging approximately 27.22 and 31.68 million years ago (Ma), respectively. Whole-genome duplication (WGD) analysis revealed an ancient duplication event in marama. Gene family analysis revealed expanded families enriched in pathways related to stress adaptation, energy metabolism, and environmental signaling, including the spliceosome, citrate cycle, and carbon fixation pathways. These findings highlight marama’s resilience to arid environments. In contrast, contracted gene families associated with secondary metabolite biosynthesis and defense pathways suggest a trade-off, potentially due to reduced pathogen pressure. Marama-specific genes were enriched in amino acid catabolism pathways, potentially playing roles in stress signaling and energy regulation. Core gene families shared with other legumes were enriched in conserved pathways, such as photosynthesis and hormone signaling, which are fundamental for plant growth and survival. Population analysis of geographically diverse samples revealed two distinct clusters, though phenotypic differences remain unclear. Overall, this study presents the first high-quality genome assembly of marama bean, offering a valuable genomic reference for understanding its unique biology and highlighting its potential for crop improvement in challenging environments.